Don't We Need Non-communicable Diseases Block in Government Tertiary Care Hospitals? - Sumanth Mallikarjuna Majgi; Purushottam A. Giri; Bhavani Nivetha (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
Non-communicable Diseases (NCDs) are emerging as the major cause of morbidity and mortality globally. In India, non-communicable diseases (NCDs) contribute to around 5.87 million deaths that account for 60% of all deaths. India shares more than two-third of the total deaths due to NCDs in the South-East Asia Region. World Health Assembly endorsed the WHO Global Action Plan for the Prevention and Control of NCDs for 2013-2020, the goal is to reduce the preventable and avoidable burden of morbidity, mortality and disability due to non-communicable diseases by means of multi-sectoral collaboration and  cooperation at national, regional and global level. When analyzed about the existing health care services in India, the primary health centers are the fi rst point of contact for a patient with the health care, the services provided in the primary Health centers are grossly inadequate, in India almost 40% of the primary health centers are functioning without lab technician and 9% without doctors. In order to improve the NCD services in a tertiary care, we have to address the issue of dissatisfaction in patients in tertiary care by providing a better organized service which will lead to better compliance of the patient to treatment.